A perceptual pathway for voicing-conditioned vowel duration. Issue 1 (28th October 2020) - Sanker, Chelsea
When codas and vowels are cross-spliced, vowels originally produced with voiced codas are perceived as longer than vowels of the same duration produced with voiceless codas. The spliced coda has the opposite effect: Vowels presented with voiced codas are perceived as shorter. To explain what characteristics make vowels produced with voiced codas sound longer than vowels produced with voiceless codas, four experiments tested how acoustic correlates of voicing affect English speakers' perception of vowel duration. Vowels were manipulated in a ten-step duration continuum, and listeners categorized each vowel as 'long' or 'short.' Study 1 tested effects of vowel height categories (/æ, ɛ, ɪ/) and within-category F1. Study 2 tested effects of intensity contour. Study 3 tested effects of spectral tilt. Perceived vowel duration increased with vowel height and rising intensity. Perceived vowel duration decreased with falling intensity and with higher spectral tilt. There was no effect of within-category F1. Study 4 confirmed that the effect of the original coda environment is not specific to English stimuli. The effects of spectral tilt and intensity contour on perceived duration provide a possible perceptual pathway for the development of voicing-conditioned vowel duration; coda voicing influences these characteristics and they in turn influence perceived vowel duration.